Excess commuting and frictions in the labor market - Nick Deschacht; Karolien De Bruyne (Journal of Applied Economics, 2020)
We propose a model of excess commuting based on search costs in the labor market and show how the equilibrium rate of excess commuting is determined by the degree of geographical job concentration - without neglecting the importance of the size of the labor market and commuting costs. We test - and largely confirm - the main predictions of our model using Belgian population data on commuting flows between all its 589 municipalities. Our approach is to aggregate the data into 640 sectors and skill-specific groups in order to generate heterogeneity in the excess commuting rate. We find that workers in sectors with a high degree of job concentration have lower rates of excess commuting and that workers that operate in larger labor markets, such as higher educated workers and men compared to women, have higher rates of excess commuting.
Keywords: 330; Excess commuting; job search